A Study on the Applications of Number Theory in Mathematics: Exploring Applications and Concepts in Number Theory (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A few interesting applications have been made for Number Theory in Statistics. The reason for this overview paper is to feature certain significant uses of this sort. Prime numbers are an intriguing and testing field of mathematical hypothesis research. Diophantine conditions are the focal piece of number hypothesis. The condition that requires indispensable arrangements is known as the Diophantine condition. A few issues identified with prime numbers and the function of Diophantine conditions in Design Theory are talked about in the initial segment of this paper. The commitment of Fibonacci and Lucas numbers to the semi leftover plan of Metis is clarified. The Discrete Logarithm issue is a well-known issue identified with limited fields. The structure of Discrete Logarithm is examined in the second piece of this paper.